Ba2Cd(B3O6)2: A Congruent‐Melting Compound with Isolated B3O6 Units1. Issue 6 (26th April 2013) - Dong, Xiaoyu; Cui, Liang; Shi, Yunjing; Pan, Shilie; Zhou, Zhongxiang; Yang, Zhihua; Zhang, Bingbing; Jiang, Xiangzhan; Yang, Yun; Chen, Zhaohui; Huang, Zhenjun
Abstract The single crystals of Ba2Cd(B3O6)2 were grown by the spontaneous crystallization method for the first time. They crystallize in the centrosymmetric trigonal space group R <![CDATA[$\bar{3}$]]> <inline-graphic xlink:href="ark:/27927/pgg20q12fq3" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> with a = 7.143(3) Å, c = 17.405(16) Å, and Z = 3. The structure is characterized by isolated B3O6 units, and the Ba2+ and Cd2+ cations connect with B3O6 rings to form three dimensional structure. The TG/DSC and XRD results reveal that Ba2Cd(B3O6)2 melts congruently. First‐principles electronic structure calculation performed with the density functional theory (DFT) method shows that the calculated bandgaps are 4.66 eV, which is in good agreement with the UV/Vis/NIR experimental value 4.59 eV. The calculation shows that the Ba2Cd(B3O6)2 crystal has a large birefringence (Δn = 0.0875–0.0569 from 270 nm to 2600 nm), which demonstrates that Ba2Cd(B3O6)2 is a potential birefringence crystal.